Bagaimana Kualitas Pelayanan dan Fasilitas Belajar dapat Mempengaruhi Loyalitas Mahasiswa dengan Mediasi Kepuasan Mahasiswa? - Klinik Publikasi; Ongen Stembri Pattiwaellapia (Entrepreneurship Faculty, Universitas Garut, 2020)
This study aims to analyze the effect of service quality and learning facilities on student loyalty mediated by student satisfaction. The subjects of this study were students of the Magister Management of the National Development University “Veteran” Yogyakarta. This research includes a quantitative approach with a survey method. Collecting data in this study using a questionnaire with a Likert scale. The data analysis method used was SmartPLS 3.0. Results 1) The effect of service quality directly has a positive effect on student loyalty by 0.002 but not significant because the T-statistic is 0.008 <1.96 and the P-value is = 0.994> 0.05. Thus the quality of service does not have a significant effect on student loyalty of Master of Management at the National Development University “Veteran” Yogyakarta. 2) The effect, learning facilities have a positive effect on student loyalty of 0.339 but not significant because the T-statistic is 1.218 <1.96 and the P-value is = 0.226> 0.05. Thus, learning facilities do not have a significant effect on the loyalty of students of Master of Management at the National Development University “Veteran” Yogyakarta. 3) Influence, learning facilities have a positive effect on student loyalty by 0.339 but not significant because the T-statistic is 1.218 <1.96 and the P-value is = 0.226> 0.05. Thus, learning facilities do not have a significant effect on the loyalty of students of Master of Management at the 'Veteran' National Development University Yogyakarta. 4) The effect of learning facilities in this case has a positive and significant effect on student loyalty by mediating student satisfaction of 0.192 (T-Statistics = 1.984 and P-value = 0.048). The estimation results of the mediation test show that student satisfaction can mediate the effect of learning facilities on student loyalty because the T-statistic is greater than 1.96, namely 1.984 and the P-value = 0.048 is smaller than the P-value 0.05. It can be interpreted that there is an effect of learning facilities on student loyalty which is mediated by student satisfaction.